Estimation of Aspect Ratio Values in Carbonate Rocks Using the Kuster–Toksöz Model for Reservoir Characterization - Hasanah, Uswatun; Winardhi, Ignatius Sonny (UIR PRESS, 2024)
Carbonate reservoirs are known for their complex pore structures, which significantly affect their elastic properties and, consequently, their fluid storage and flow capacities. Traditional models often fail to capture the heterogeneous pore geometries in carbonate rocks accurately. The Kuster-Toksöz model offers a means to estimate effective elastic moduli by incorporating pore aspect ratios, providing a more nuanced understanding of pore shapes and distributions The combination of Kuster Toksӧz inclusion model for pore shape of penny cracks produces velocity model which is then compared with the measurement results. The results show a good match at 2800 m - 3000 m intervals with a single aspect ratio of 0.05. The difference in the aspect ratio of each depth is related to the compacting process of rock formation due to increased depth, which shows that the deeper the depth the rock pore will be stiffer.